Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có: \(x^2\left(x+4\right)^2-\left(x+4\right)^2-\left(x^2-1\right)\)
\(=\left(x+4\right)^2.\left(x^2-1\right)-\left(x^2-1\right)\)
\(=\left(x^2-1\right)\left(\left(x+4\right)^2-1\right)\)
\(=\left(x-1\right)\left(x+1\right)\left(x+4-1\right)\left(x+4+1\right)\)
\(=\left(x-1\right)\left(x+1\right)\left(x+3\right)\left(x+5\right)\)
Cho mình nhé hihi!!!
x2(x+4)2-(x+4)2-(x2-1)
=(x+4)2 (x2-1)-(x2-1)
=(x2-1)(x2+8x+16-1)
=(x-1)(x+1)(x2+8x+15)
1) = \(x^2-1=\left(x-1\right)\left(x+1\right)\)
2) \(=\left(x^2+8\right)^2-16x^2=\left(x^2-4x+8\right)\left(x^2+4x+8\right)\)
3)
\(=x^4-x+x^2+x+1=x\left(x^3-1\right)+x^2+x+1=x\left(x-1\right)\left(x^2+x+1\right)+x^2+x+1=\left(x^2+x+1\right)\left(x^2-x+1\right)\)
4) \(=x^5-x^2+x^2+x+1=x^2\left(x-1\right)\left(x^2+x+1\right)+x^2+x+1=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
1.\(x^2-2021+2020=x^2-1=\left(x+1\right)\left(x-1\right)\)
2. \(x^4+64=\left(x^2-4x+8\right)\left(x^2+4x+8\right)\)
3. \(x^4+x^2+1=\left(x^2+x+1\right)\left(x^2+x+1\right)\)
4. \(x^5+x+1=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
1/ = x4 + 2x3 + 4x2 + 3x - 10 = (x4 - x3) + (3x3 - 3x2) + (7x2 - 7x) + (10x - 10)
= (x - 1)(x3 + 3x2 + 7x + 10) = (x - 1)[(x3 + 2x2) + (x2 + 2x) + (5x + 10)]
= (x - 1)(x + 2)(x2 + x + 5)
2/ = (x5 - 2x4) + (x4 - 2x3) + (x3 - 2x2) + (x2 - 2x) + (x - 2) = (x - 2)(x4 + x3 + x2 + x + 1)
x2+(2a+b)xy+2aby2
=x2+2axy+bxy+2aby2
=(x2+bxy)+(2axy+2aby2)
=x(x+by)+2ay(x+by)
=(x+by)(x+2ay)
\(8xy^3+x\left(x-y\right)^3\)
\(=x\left[8y^3+\left(x-y\right)^3\right]\)
\(=x\left[\left(2y\right)^3+\left(x-y\right)^3\right]\)
\(=x\left(2y+x-y\right)\left[\left(2y\right)^2-2y\left(x-y\right)+\left(x-y\right)^2\right]\)
\(=x\left(x+y\right)\left(4y^2-2xy+2y^2+x^2-2xy+y^2\right)\)
\(=x\left(x+y\right)\left(7y^2+x^2-4xy\right)\)
Đặt: x - y = a ; 3x + y - z = b ; -4x + z = c
Ta có: a + b + c = x - y + 3x + y - z - 4x + z = 0
Khi đó: \(\left(x-y\right)^3+\left(3x+y-z\right)^3+\left(-4x+z\right)^3\)
= \(a^3+b^3+c^3\)
= \(\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc+ac\right)+3abc\)
= \(0.\left(a^2+b^2+c^2-ab-bc+ac\right)+3abc\)
= \(3abc\)
= \(3\left(x-y\right)\left(3x+y-z\right)\left(-4x+z\right)\)
ta có :
\(x^2+0,25-x=x^2-2.\frac{1}{2}.x+\frac{1}{2^2}=\left(x-\frac{1}{2}\right)^2\)